2018
DOI: 10.5334/cstp.101
|View full text |Cite
|
Sign up to set email alerts
|

Getting it Right or Being Top Rank: Games in Citizen Science

Abstract: The use of games in citizen science is growing, but can create tension as gaming and science can be seen as incompatible areas of activity. For example, the motivations for winning a game and scientific pursuit of knowledge may be seen as contrary. Over a one-year period, we conducted a virtual ethnographic study of the public forums of two online citizen science projects, Foldit and Galazy Zoo, the first a project in which gaming is an explicit design feature and the second in which it is not. The aim was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, the question remains as to what extent play helps people deliberate about and commit to solutions (Glas et al 2019). In our case, the game-like features and structures of the protein demonstrations, such as competition, rules, and time pressure (see Read and Reeves 2009;Ponti et al 2018), enabled us to observe changing modes of interaction compared to only tasting the foods. While the situations created by our demonstrative acts unfolded in a specific way during the game playing, the students were able to encounter the new foods, relate to them, and reflect on their eating through a different register of interaction than merely through the experience of taste.…”
Section: Play As a Mode Of Public Engagementmentioning
confidence: 84%
“…However, the question remains as to what extent play helps people deliberate about and commit to solutions (Glas et al 2019). In our case, the game-like features and structures of the protein demonstrations, such as competition, rules, and time pressure (see Read and Reeves 2009;Ponti et al 2018), enabled us to observe changing modes of interaction compared to only tasting the foods. While the situations created by our demonstrative acts unfolded in a specific way during the game playing, the students were able to encounter the new foods, relate to them, and reflect on their eating through a different register of interaction than merely through the experience of taste.…”
Section: Play As a Mode Of Public Engagementmentioning
confidence: 84%
“…Motivations may be context specific; for example, users of two different ''distributed-mind'' projects (foldit and GalaxyZoo, designed to find folding solutions for proteins and to classify images of galaxies, respectively) had contrasting views on the desirability of gamification. 91 The needs of end users also differ; for some applications, such as monitoring trends over time, retention of existing observers who carry out repeat visits to the same sites may be more important than the recruitment of new ones. 87 The incentives required to support retention might be quite different from those enhancing recruitment.…”
Section: Aligning Incentives For Planners Observers and Usersmentioning
confidence: 99%
“…Overall, knowing what, if any, ll OPEN ACCESS incentives could be offered requires a good understanding of the motivations of participants. 91 If direct questioning of observers is not possible, 93,94 this might be done by analyzing the composition of recorded data in order to determine which external factors drive particular types of participation. 61,95 Designers of messy-data-collection programs should also be aware that incentives can be counterproductive.…”
Section: Aligning Incentives For Planners Observers and Usersmentioning
confidence: 99%
“…In Table 1, it can be observed that more than 80% of users belong to the first group and also covered a total of 1,492 of the images analyzed, which represents 70% of the total. These indicators reflect, although it is not relevant in the validation of the method, that most users leave the experiment promptly, after few executions, mainly because the experiment needs to be improved to be more attractive to users, through gamification techniques that motivate or reward them, as proposed by [37] [38].…”
Section: B Second Approach: Integrating a Reputation Systemmentioning
confidence: 99%